How to measure urban water security? An introduction to the Water Security Assessment Tool (WATSAT) - Mukand Babel; Kaushal Chapagain; Victor Shinde (APN Science Bulletin, 2023)
The objective of the project was to develop a web-based digital tool called the Water Security Assessment Tool (WATSAT) to help city authorities and decision-makers make an objective evaluation of the water security situation in the city. It uses an indicator-based methodology that measures five distinct dimensions (broad elements) of water security: “Water supply and sanitation”, “Water productivity”, “Water-related disasters”, “Water environment”, and “Water governance”, which together culminate into a Water Security Index (WSI). The tool is developed based on the water security assessment framework developed by Babel, Dang, Sharma, and Shinde (2015). WATSAT results in a quantitative assessment of water security in a city, wherein the WSI provides an overall picture of the water security situation in a city, while the evaluation of the various dimensions helps identify areas of concern. WATSAT aids city authorities in having a holistic understanding of water security and interconnections of various factors affecting it and assists them in informed decision-making to arrive at system-based interventions to tackle water security threats in the cities.